REGIONAL MOUNTAIN AND MOUNTAIN AREAS AS A MEANS OF REGULATING TERRITORIAL DEVELOPMENT (Scientific electronic journal "Labor Economics and Human Capital", 2023)
The article discusses the foreign practice of using regionalization as a means of regulating territorial development. It is known that the order of regionalization of regions is always purposeful and serves to solve many problems of socio-economic development of regions. Also, in solving the problem of reducing the unevenness of the development of mountain and sub-mountain regions, the need to take into account the supply of internal resources of the region is based, the feasibility of regionalization of problematic resources is emphasized, and the methodology of its implementation is proposed.
Keywords: territory, climate, resource, industry, demographic, labor, finance, infrastructure, investment.